2020
DOI: 10.1101/2020.01.27.920728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irrelevant Predictions: Distractor Rhythmicity Modulates Neural Encoding in Auditory Cortex

Abstract: Dynamic Attending Theory suggests that predicting the timing of upcoming sounds can assist in focusing attention towards them. However, whether similar predictive processes are also applied to background noises and assist in guiding attention away from potential distractors, remains an open question.Here we address this question by manipulating the temporal predictability of distractor sounds in a dichotic listening selective attention task. We tested the influence of distractors' temporal predictability on pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
2
2
0
Order By: Relevance
“…Additional brain regions, such as the PPC, are also engaged in representing some aspects of the linguistic structure of task-irrelevant speech, which we interpret as maintaining a representation of what goes on in the 'rest of the environment', in case something important arises. Importantly, similar interactions between the structure of task-irrelevant sounds and responses to the to-be-attended sounds have been previously demonstrated for non-verbal stimuli as well (Makov and Zion Golumbic 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Additional brain regions, such as the PPC, are also engaged in representing some aspects of the linguistic structure of task-irrelevant speech, which we interpret as maintaining a representation of what goes on in the 'rest of the environment', in case something important arises. Importantly, similar interactions between the structure of task-irrelevant sounds and responses to the to-be-attended sounds have been previously demonstrated for non-verbal stimuli as well (Makov and Zion Golumbic 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Additional brain regions, such as the PPC, are also engaged in representing some aspects of the linguistic structure of task-irrelevant speech, which we interpret as maintaining a representation of what goes on in the ‘rest of the environment’, in case something important arises. Importantly, similar interactions between the structure of task-irrelevant sounds and responses to the to-be-attended sounds have been previously demonstrated for non-verbal stimuli as well (Makov and Zion Golumbic 2020). Together, this highlights the fact that attentional selection is not an all-or-none processes, but rather is a dynamic process of balancing the resources allocated to competing input, which is highly affected by the specific perceptual, cognitive and environmental aspects of a given task.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, a large body of work demonstrates that the brain exhibits reduced responses to regular, predictable stimuli (de Lange et al, 2018;Itti and Baldi, 2009;Richter et al, 2018), interpreted as reflecting the fact that the detection of regular structure facilitates the conservation of processing and computational resources. Indeed, it has been shown that regular patterns are easier to process (Rohenkohl et al, 2012) and also, critically, easier to ignore (Andreou et al, 2011;Southwell et al, 2017;Makov and Zion Golumbic, 2020) which has been taken as evidence that regularity does not draw on attentional resources.…”
Section: Introductionmentioning
confidence: 99%